(untitled) (Philologia, 2021)
“Every novel is a form of quest”, says John Fowles in The Tree. As one of Fowles’s critics William Palmer claims, ”all Fowlesian protagonists are questers.” Daniel, the protagonist of Daniel Martin, also journeys towards selfhood. Daniel is a writer and, for this reason, his quest for self-awareness affects in a signiﬁcant way his creativity: he pursues the road of individuation in order to be able to create. The hero-quester who quests under the inﬂuence of archetypes in order to ﬁnd his own self recalls the ideas of Joseph Campbell and Carl Jung. Fowles makes use of the same model of the hero’s quest in his prose. An interesting aspect of Daniel Martin is the notion of time expressed in the narrative. Fowles shows us in this novel how, as in that line of Eliot, ”the timeless intersecting with time”, as a result of the play of archetypes occurs. The purpose of this paper is to show how Fowles exploits the quest motif in his ﬁction.